Pengembangan Budaya Literasi untuk Meningkatkan Minat Baca Siswa di SDN 195/VI Pematangan Kancil Merangin Jambi - Fitriya, Afifa Hana; Nofriani, Endang; Febiati, Diah; Afifah, Putri; Safitri, Eny; Salsabillah, Shella (TSAQOFAH, 2023)
The literacy skills possessed by students in Indonesia are quite worrying. Based on the data recorded in PISA, the score obtained by Indonesia regarding literacy is only 371. Indonesia is ranked third from the bottom regarding literacy. The purpose of writing this journal is to critically examine the literacy of students at SDN 195/IV Pematangan Kancil Merangin Jambi. This research was conducted at SDN 195/VI Pematang Kancil Merangin Jambi. The subjects of this study were students of SDN 195/VI Pematang Kancil Merangin Jambi. The research subjects were selected at the elementary school level because based on the results of field observations, the literacy level of students at SDN 195/VI Pematang Kancil Merangin Jambi was still very minimal or low. The writing of this journal is based on the type of qualitative research using a literature review approach. Literature review is an activity to examine various forms of relevant sources. The conclusion from the scientific literacy analysis activities at SDN 195/VI Pematang Kancil Merangin Jambi has a low literacy level. One of the influencing factors is environmental factors. The SDN 195/VI school is located in a small village, where the accreditation owned by the school is accreditation C. There are various ways to improve literacy in students, one example is by creating a literacy corner movement program. Based on the research conducted, it is effective and efficient to improve student literacy.